La métaphrase du Martyre de S. Aréthas (BHG 166y) Entre les Actes anciens (BHG 166) et Syméon Métaphraste (BHG 167) - Detoraki, Marina (Analecta Bollandiana, 2002)
The Passion of St. Arethas conserved in the codex 2 of the Protaton of Mount Athos (BHG 166y) is a unique metaphrastic version which, as shown in this paper, should be placed between the ancient Passion (BHG 166) and the Metaphrasis made by Symeon (BHG 167). Apparently this text served as a model for Symeon in his metaphrasis of the Passion of St. Arethas. In these terms it provides evidence of intermediate versions now lost.